2019
DOI: 10.1002/jcb.29318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on glioma cells in the presence or absence of cisplatin

Abstract: With the extensive use of dexmedetomidine (Dex) in the surgical resection of tumours for its potent sedative and analgesic properties, its effects on various properties of tumours have received increased attention. The study described herein aimed to investigate the effects of Dex on glioma cells in the presence or absence of cisplatin (DDP). Glioma U251 and U87MG cells were treated with different doses (1‐50 nM) of Dex for 12 hours, then recultured in a Dex‐free medium. In addition, Dex was added to U251 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…DEX facilitated cell proliferation and migration and up regulated anti-apoptotic proteins in lung carcinoma and neuro glioma cells [25] . In addition, DEX had obvious influence on glioma cell proliferation in the presence or absence of cisplatin [8] . Whereas, the underlying mechanisms of DEX in glioma growth remain elusive.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…DEX facilitated cell proliferation and migration and up regulated anti-apoptotic proteins in lung carcinoma and neuro glioma cells [25] . In addition, DEX had obvious influence on glioma cell proliferation in the presence or absence of cisplatin [8] . Whereas, the underlying mechanisms of DEX in glioma growth remain elusive.…”
Section: Resultsmentioning
confidence: 96%
“…DEX has been attested to facilitate breast cancer cell malignant behaviors [6,7] . Moreover, DEX at 10 nm could aggrandize the proliferation of both glioma U251 and U87MG cells [8] . Nevertheless, the underlying mechanism of DEX on glioma tumourogenesis is needed to be explained.…”
mentioning
confidence: 96%
“…First in vitro and in vivo studies reported paradoxical results in thus far that DEX induced concentration-dependent and cell type-specific effects that often were divergent with respect to their oncological outcome. 22 , 29 Nevertheless, when employed at clinically relevant concentrations through continuous infusion, DEX tends to promote antineoplastic effects and hence impairs the proliferation, invasiveness and survival of malignant cells. 27–39 , 43 , 44 In addition, treatment of distinct types of tumors with DEX significantly limited inflammasome activation, thus decreasing the secretion of IL-1β that is mostly considered as a protumorigenic cytokine.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 32 Some studies also reported an extracellular regulated kinase (ERK) 1/2-dependent inhibition of the c-MYC oncogene, which is amplified in various types of cancer and promotes invasiveness and proliferation. 29 , 34 It is worth noting that most DEX-mediated antitumor effects are provoked by epigenetic changes such as the modification of the expression of non-coding RNAs including miRNAs, circRNAs and lncRNAs. Thus, DEX activates the miR-143-3p/epidermal growth factor receptor (EGFR) pathway substrate 8 axis, 28 increases miR-493-5p, which targets RASL11B implicated in cancer development, 30 decreases the expression of miR-1307, 31 upregulates miR-185, which inactivates the Sry (sex determining region Y)-box 9 (SOX9)/Wnt/B-catenin pathway 32 and miR-520a-3p that targets the metastases-inducing gene Yod 1 coding for the deubiquitinating enzyme YOD1.…”
Section: Introductionmentioning
confidence: 99%